Public Satisfaction With HGB Extension Services at the BPN Regional Office of Jawa Timur Province - Sintya Ari Putri Nugraha (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Public services consist of administrative services, provision of goods, and services. The extension of Building Use Rights (HGB) is a form of administrative service under the authority of the National Land Agency. Given that HGB has a specific time limit, the extension process is an important aspect in ensuring legal certainty over land rights. The purpose of this study is to assess the level of public satisfaction with HGB extension services at the East Java Provincial BPN Office by reviewing aspects of service speed, information disclosure, officer competence, availability of facilities and infrastructure, and responsiveness to complaints. The research approach applied in this study is descriptive quantitative, with data obtained through questionnaires given to 100 applicants for HGB extension, supported by literature studies and field observations. Instrument testing proved that all research indicators had an excellent level of validity and reliability, as indicated by a Cronbach's Alpha value of 0.96. Based on descriptive analysis, the level of public satisfaction was in the fairly satisfied category, although there were still several aspects that needed improvement, particularly related to the timeliness of services, clarity of procedures, and the condition of service facilities.